Fermentation Of Recombinant E. coli TOP10F' / pPROEX tm HTa / BmSXP To Achieve High Yield Of Biomass And Recombinant Antigen For Diagnostic Application - Khoo , Teng Kew (2011)
panLF Rapid™ is a rapid IgG4 antibody detection test which is based on the detection of anti-filarial IgG4 antibodies that react with recombinant B. malayi antigens, BmR1 and BmSXP. This diagnostic kit is very useful for the detection of lymphatic filariasis (LF), especially in assisting the WHO on its certification and surveillance activities of post-mass drug administration that is in relation to its ‘Global Programme to Eliminate Lymphatic Filariasis’ effort.